2019
DOI: 10.1093/mnras/stz3420
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-simultaneous radio and X-ray observations of Aql X-1 : probing low luminosities

Abstract: Aql X-1 is one of the best-studied neutron star low-mass X-ray binaries. It was previously targeted using quasi-simultaneous radio and X-ray observations during at least 7 different accretion outbursts. Such observations allow us to probe the interplay between accretion inflow (X-ray) and jet outflow (radio). Thus far, these combined observations have only covered one order of magnitude in radio and X-ray luminosity range; this means that any potential radio-X-ray luminosity correlation, L R ∝ L X β , is not w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 55 publications
(112 reference statements)
0
23
0
Order By: Relevance
“…Tremou et al (2020) for a recent discussion), the picture is more complicated in the case of NS systems. The correlation has been studied in depth in only a few individual systems (Migliari et al 2003;Tudose et al 2009;Tetarenko et al 2016a;Gusinskaia et al 2020), with different values of the power-law index proposed by different groups and in different sources. More recently a 'universal' NS correlation index of 0.44 has been suggested (Gallo et al 2018, although see Tudor et al 2017.…”
Section: Radio Emission Correlationsmentioning
confidence: 99%
“…Tremou et al (2020) for a recent discussion), the picture is more complicated in the case of NS systems. The correlation has been studied in depth in only a few individual systems (Migliari et al 2003;Tudose et al 2009;Tetarenko et al 2016a;Gusinskaia et al 2020), with different values of the power-law index proposed by different groups and in different sources. More recently a 'universal' NS correlation index of 0.44 has been suggested (Gallo et al 2018, although see Tudor et al 2017.…”
Section: Radio Emission Correlationsmentioning
confidence: 99%
“…XB 1832-330 is a persistent X-ray source, and its deep radio upper limit at L X ∼ 2 × 10 35 is among the most constraining observed at this L X , comparable to that seen in Aql X-1 during its fading after an outburst (Gusinskaia et al 2020b). As in Aql X-1, the XB 1832-330 data are consistent either with a steep radio/X-ray correlation for this binary or with a quenching of the jet at this luminosity.…”
Section: Ac 211mentioning
confidence: 76%
“…Dark green circles show quiescent/hard state black holes. Quiescent/hard state neutron stars are shown as blue squares, with additional data points from Aql X-1 (Gusinskaia et al 2020b), and soft sources shown as orange pluses from (Ludlam et al 2019). Pink stars are accreting millisecond X-ray pulsars and light green triangles are transitional millisecond X-ray pulsars.…”
Section: Results For Individual Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jets from accreting NS LMXBs show a diverse range of behaviour (e.g., Migliari & Fender 2006;Migliari 2011;Tudor et al 2017;Gusinskaia et al 2017;Gallo et al 2018;Russell et al 2018;Gusinskaia et al 2020), and there has been some debate as to whether NS LMXB jets show a similar pattern of behaviour to BH systems (see, e.g., Migliari & Fender 2006;Marino et al 2020) NS and BH LMXBs can launch two types of jets depending on the state of the source: a steady compact jet or a bright transient jet (e.g., Migliari & Fender ★ E-mail:thomas.russell@inaf.it 2006), depending on the mass accretion rate ( ) and structure of the accretion flow. At lower during the harder X-ray spectral states the compact jet is characterised by optically-thick synchrotron emission exhibiting a flat to inverted radio spectrum ( ∼ 0, where the radio flux density, , is proportional to the observing frequency, , such that ∝ ; Blandford & Königl 1979).…”
Section: Introductionmentioning
confidence: 99%